Elites and Social Change - Khebache , Fatiha (Journal of Ecohumanism, 2025)
This article aims to shed light on the role of the intellectual in Arab societies, positioned between the challenges of meeting daily material needs and the fulfillment of their ethical obligation to effect positive change within their community. Owing to the scientific status that grants them social responsibility, intellectuals—considered members of the elite—possess the capacity for critical thinking and scientific analysis of societal realities. These qualities enable them to participate in decision-making, disseminate awareness and knowledge, and contribute to development by critiquing the status quo and advocating for change through scientifically grounded solutions and alternatives.